EFFECTS OF ACUTE HYPOXIA ON HEMODYNAMICS IN DOGS - Ullah, Farman; Ali, Shaukat (Journal of Ayub Medical College Abbottabad, 2000)
Background: Almost 50 years ago tire proposition that acute hypoxia elicits pulmonary vasoconstriction was made. By now methods have been standardised for exploring the pulmonary and systemic circulation in a systematic & sophisticated way and tire introduction of cardiac catheterization had brought the previous remote pulmonary circulation within reach. Methods: This study was designed to see the effects of acute hypoxia on hemodynamics with the advanced, sophisticated equipment and standardised method. The effects of acute 10 minutes’ hypoxia were studied on hemodynamics in anaesthetized dogs. Results: Acute hypoxia increased the Cardiac Output from 1.76 ± 0.43 to 1.91 ± 0.52 L/min. HR from 240 ± 55.58 to 260 ± 63.34 beat/min, Ppa from 2.24 ± 0.61 to 3.39 ± 1.09 kPa, PVR from 9.49 ± 3.33 to 14.30 ± 5.29 kPa. s/L, Psa from 14.53 ± 1.16 to 15.16 ± 1.17 kPa. SVR from 61.50 ± 14.81 to 64.33 ± 15.02 kPa. s/L and CBF from i73.62 ± 81.99 to 192.50 ± 85.40 ml/min, respectively. Conclusions: The results showed that Acute hypoxia increased all the parameters but the increase in pulmonary vascular resistance was more significant than systemic vascular resistance. This shows that in vivo the hypoxic response of cerebral vessel is dilative, while the hypoxic response of pulmonary vessels as well as that of peripheral systemic vessel is constrictive. Key Words: Hypoxia, Hemodynamics.